METHODOLOGICAL AND PRACTICAL GUIDELINES FOR THE DEVELOPMENT OF ENVIRONMENTAL ENTREPRENEURSHIP WITHIN THE FRAMEWORK OF PUBLIC-PRIVATE PARTNERSHIP - TULAI, Oksana; KNIAZ, Sviatoslav; SKRYNKOVSKYY, Ruslan; PAVLENCHYK, Nataliia; PAVLENCHYK, Anatolii (Journal of European Economy, 2022)
Given the severity of the environmental problems that the world is facing, it is clear that to ignore the principles of sustainable development is both irresponsible and unjustifiable in any sector of a national economy. Although right now environmental enterprises stand out among business entities, there is every reason to believe that eventually all economic actors will have to attain attributes that prove their adherence to the sustainable development principles. Environmental entrepreneurship is, in fact, a qualitative feature of entrepreneurship in general. At the present stage of social development, corporate social responsibility is largely environmental by nature. The paper aims to develop a set of methodological and practical guidelines for the development of environmental entrepreneurship within the framework of public-private partnerships. This has never been done before in such a context and thus constitutes the paper’s scientific contribution, as unlike the existing guidelines, this particular set is established by identifying and ordering the structural elements of environmental entrepreneurship and distinguishing its development stages. JEL: Q5.